Geographical and temporal patterns of rabies post exposure prophylaxis (PEP) incidence in humans in the Mekong River Delta and Southeast Central Coast regions in Vietnam from 2005 to 2015 - Hu Suk Lee; Vu Dinh Thiem; Dang Duc Anh; Tran Nhu Duong; Mihye Lee; Grace, Delia; Hung Nguyen-Viet (Public Library of Science, 2018)
Background In Vietnam, rabies has been a notifiable disease for more than 40 years. Over the last five years, on average, more than 350,000 people per year have been bitten by dogs and cats while more than 80 human deaths have been reported yearly. No studies have been conducted to evaluate the geographical and temporal patterns of rabies in humans in Vietnam. Therefore, the main objective of this study was to assess the geographical and temporal distributions of rabies post exposure prophylaxis (PEP) incidence in humans in Vietnam from 2005 to 2015. Methods Average incidence rabies (AIR) PEP rates for every 3 or 4 years (2005–2008, 2009–2012 and 2013–2015) were calculated to describe the spatial distribution of rabies PEP. Hotspot analysis was implemented to identify patterns of spatial significance using the Getis-Ord Gi statistic. For temporal pattern analysis, two regions [Mekong River Delta (MRD) and Southeast Central Coast (SCC)], with the highest incidence rates, and the seasonal-decomposition procedure based on loess (STL), were compared to assess their temporal patterns of rabies PEP. Findings We found hotspots in southern Vietnam and coldspots in northern Vietnam during the study period. Rabies cases were limited to specific areas. In addition, the hotspot analysis showed that new risk areas were identified in each period which were not observed in incidence rate maps. The seasonal plots showed seasonal patterns with a strong peak in February/July and a minor peak in October/December in the MRD region. However, in the SCC, a small peak was detected at the early part of each year and a strong peak in the middle of each year. Conclusion Our findings provide insight into understanding the geographical and seasonal patterns of rabies PEP in Vietnam. This study provides evidence to aid policy makers when making decisions and investing resources. Such information may also be utilized to raise public awareness to prevent rabies exposures and reduce unnecessary PEP.